PENDUGAAN STOK KARBON DAN SERAPAN KARBON PADA TEGAKAN MANGROVE DI KAWASAN EKOWISATA MANGROVE DESA MOJO KABUPATEN PEMALANG - Rifandi, Raditya Ahmad (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
The potency for mitigating climate change is owned by mangrove forests because of their ability to store and absorb large amounts of carbon for a long time. Based on this potency, it is necessary to conserve mangrove areas, by maintaining the land as the carbon storage for future generations, by natural approaches, such as reforestation, and by engineering technology, such as building a seawall. The research aims to estimate biomass, carbon storage, and the ability of mangroves to absorb carbon from mangrove tree stands, as the main vegetation that makes up mangrove forests. The results can be the references to maintain mangrove ecosystems. The sampling method is purposive sampling in 4 stations with 20 total sample points, which represent the overall characteristics of the vegetation in Mangrove Eco-Tourism, Mojo Village, Pemalang. Carbon stock analysis was using allometric equations to estimate carbon storage in tree stands. The results showed that there are 3 mangrove species in this area, namely Avicennia Marina, Avicennia Alba, and Rhizopora Mucronata. They each have Important Value Index of 210,7; 12,8; and 76,5. Total biomass and carbon content of mangrove stands in the entire 57,3 Ha area is about 7.070,91 tons of biomass and 3.323,33 tons of carbon storage with the ability to absorb CO2 is 12.196,61 tons/day.